Influence of Excipient Composition on Survival of Vaginal Lactobacilli in Electrospun Nanofibers - Spase Stojanov; Julijana Kristl; Špela Zupančič; Aleš Berlec (MDPI AG, 2022)
The lack of appropriate delivery systems hinders the use of probiotics in the treatment of vaginal infections. Therefore, the development of a new delivery system for the local administration of vaginal probiotics is necessary. In this study, we selected three vaginal lactobacilli, i.e., Lactobacillus crispatus, Lactobacillus gasseri, and Lactobacillus jensenii, and incorporated them into nanofibers using electrospinning. Polyethylene oxide (PEO) was used as a carrier polymer to produce nanofibers. It was supplemented with alginate and sucrose selected from a group of carbohydrates for their growth-promoting effect on lactobacilli. The interaction between excipients and lactobacilli was evaluated thermally and spectroscopically. Bacterial survival in polymer solutions and in nanofibers immediately after electrospinning and after storage varied among species and was dependent on the formulation. Sucrose improved the survival in polymer solutions and preserved the viability of L. crispatus and L. jensenii immediately after electrospinning, and L. gasseri and L. jensenii during storage. Blending PEO with alginate did not improve species viability. However, the three lactobacilli in the nanofibers retained some viability after 56 days, indicating that composite multifunctional nanofibers can maintain the viability of vaginal lactobacilli and can be used as a potential solid delivery system for vaginal administration of probiotics.